INSTITUTIONAL INVESTMENT POLICY FRAMEWORKS FOR THE AGRICULTURE OF THE REPUBLIC OF SERBIA - Miletić, Vesna; Milosavljević, Dušan; Kostić, Boban (Economics of Agriculture, 2012)
Investments are of great importance to agriculture, which has a special role and place in the overall economic development of the Republic of Serbia. Analyses show unfavorable agricultural credit conditions, which are not in accordance with its role and its importance. The principal aim of this research is to contribute to designing optimal measures of investment policies in the Republic of Serbia. The current economic and financial crisis during the transition process and the European Union accession process caused lower foreign direct investment inflows. It is necessary to sustain agricultural competitiveness, because it will face reduction of customs barriers and ferce competition in the free European market at the moment of becoming a member of the European Union. This requires institutional support while creating attractive conditions for foreign investments, in other words more favorable credit conditions and bigger budget for investments in agriculture which offers a huge production and export potential. EU accession processes include the liberalization of the agricultural produce market, and at the same time require a secure government support for agriculture in the tradition of developed countries. Therefore, it is necessary to systematically and continuously remove the obstacles during the harmonization process of our agricultural policy and that one of the European Union countries which is characterized by its highly subsidized agricultural production. At the end of this document are given conclusions of conducted research and recommendation for improvement investments to agriculture of Serbia.